(untitled)
The statement by "D.M.H." (Historia Junior, 27, August, 1963)that the Zimbabwe Ruins were discovered by Adam Renders in 1868,cannot be sustained in the face of evidence from early accounts.One of the few substantially correct versions in English- of the difj- ovelY is by Summers in a recent publication